The Effect Of1sales Growth, Fix Assets Intensity,1and Audit Quality On Tax Avoidance - Sabrina Regita Dea Putri; Dudi Pratomo (Telkom University, 2025)
This research aims to determine the influence of sales growth, fixed asset intensity, and audit quality on tax avoidance in mining sector companies listed on the Indonesia Stock Exchange (BEI). The sample for this research is 9 banking companies with а total sample of 45. The results of this research show that sales growth and fixed asset intensity have a negative effect on tax avoidance, while audit quality has a positive effect on tax avoidance. This research was conducted to contribute to mining sector companies so that they do not engage in tax avoidance because it will have an impact on state income.